Purchase Decision of Customers of Steel - Tamil Nadu - N. Ragothaman; S. Vasantha (International Journal of Supply Chain Management, 2018)
Abstract: Purpose: Steel is one of the core infrastructure product, whose per capita consumption indicates the Industrial development of a nation. The average per capita consumption of steel in India is at a level of 30% of the the world per capita consumption. This article attempts to examine the relationship between different dimensions of purchase decision taken by customers of steel in Tamil Nadu. This study also aims to investigate the effect of the location of the customers and their education qualification while making the Purchase decision. Design/methodology/approach: Based on literature review the impact of location and qualification of the customers on the purchase decision of steel is examined and conceptual model is developed to analyze the relationship between study variables. Simple Purposive random sampling was followed for collecting data from steel customers of Tamil Nadu Practical Implication: This research would be useful to the organization that marketing steel to understand what are the key areas to be concentrated for impacting the Purchase decision of the customer of steel in Tamil Nadu. This will help in formulating the market strategy of the customers of steel.Findings: Customers irrespective of their area of living, either urban or semi-urban, they are price conscious and expect availability of products at one source. People with higher educational qualifications have more perceptions about the factors involved in making the purchase decision. Keywords: Steel, Customers, Dimensions of Purchase decision, Location, Educational Qualification.